2012
DOI: 10.1380/ejssnt.2012.591
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Polystyrene Surface with Atomic-Scale Surface Roughness

Abstract: A new approach for fabrication of polystyrene (PS) surface with atomic-scale surface roughness is presented. The obtained surface structure was investigated using X-ray reflectivity (XR) measurements in the temperature range between room temperature and 104 • C which is close to the glass transition temperature Tg of bulk PS. At room temperature before heating, the specular XR profiles revealed a broad peak at qz = 0.04Å −1. The XR at qz = 0.04Å −1 increased with increasing temperature and showed an inflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Prior investigations into the topography of natural surfaces, including coastlines, mountains, fracture surfaces, floor tile surfaces, and atomic surfaces, indicate that the geometry of most real-world surfaces is hierarchical and even fractal-like across some length scales. Recent work on hard-carbon coatings has demonstrated that surface topography often varies significantly with size scale, such that surfaces which are nearly identical over some length scales can vary widely over other scales.…”
Section: Introductionmentioning
confidence: 99%
“…Prior investigations into the topography of natural surfaces, including coastlines, mountains, fracture surfaces, floor tile surfaces, and atomic surfaces, indicate that the geometry of most real-world surfaces is hierarchical and even fractal-like across some length scales. Recent work on hard-carbon coatings has demonstrated that surface topography often varies significantly with size scale, such that surfaces which are nearly identical over some length scales can vary widely over other scales.…”
Section: Introductionmentioning
confidence: 99%